The impact of COVID-19 on the use of fintech in managing the financial needs of tourism industry - Mohd Sam, Mohd Fazli; Ismail, Albert Feisal @ Muhd Feisal; Md. Taib, Mohd Syafiq; Alias, Siti Nur Aisyah; Bisho, Ahmed Hassan Ali Ibrahim; Mohamed, Nurul Hasyimah; Suprapto, Budi (Human Resource Management Academic Research Society, 2024)
In today's growing Malaysian economy, the tourism industry has grown to be an important component of economic activity. Because of COVID-19, tourism companies face various challenges when they do not expect cash inflows for at least three months due to ongoing national movement control (MCO) orders to prevent the spread of the COVID-19 virus. So, financial technology (Fintech) has differentiated itself from traditional businesses by breaking down barriers and bringing financial services to the public during COVID-19. The objective of this study is to identify the impact of COVID-19 on the use of Fintech in managing the financial needs of tourism companies. This study will be conducted using quantitative methodology with the involvement of the Unified Theory of Acceptance and Use of Technology (UTAUT) model as a proposed framework to study the factors that can influence consumer intention to use technology. The model was empirically tested through survey data obtained from 480 respondents. As a result, 3 out of 5 factors that have a positive relationship with behavioural intention to use Fintech, which are performance expectancy, effort expectancy, and trust, were analysed in this research. Through this study, Fintech influences tourism companies to use Fintech by trusting the service given. Several important recommendations for the government, policymakers, private sector, researchers, and knowledge are formulated.